2017
DOI: 10.1371/journal.pone.0171866
|View full text |Cite
|
Sign up to set email alerts
|

The abundance and diversity of arbuscular mycorrhizal fungi are linked to the soil chemistry of screes and to slope in the Alpic paleo-endemic Berardia subacaulis

Abstract: Berardia subacaulis Vill. is a monospecific genus that is endemic to the South-western Alps, where it grows on alpine screes, which are extreme habitats characterized by soil disturbance and limiting growth conditions. Root colonization by arbuscular mycorrhizal fungi (AMF) is presumably of great importance in these environments, because of its positive effect on plant nutrition and stress tolerance, as well as on structuring the soil. However, there is currently a lack of information on this topic. In this pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(37 citation statements)
references
References 78 publications
(97 reference statements)
2
34
0
1
Order By: Relevance
“…In combination with Fig. 8a, it is showed that most AMF biomarkers were enriched at a soil depth of 0-20 cm in samples collected from the bottom of the slope, which may be a consequence of the fact that plant residues typically accumulate on the soil surface [28,30,31], particularly on relatively at bottom slope. Such residues created high soil, nutrient content, good ventilation and hydrothermal conditions, which is very conducive to the growth of soil microorganisms.…”
Section: Relationships Between Soil Amf Diversity and Soil Propertiessupporting
confidence: 53%
“…In combination with Fig. 8a, it is showed that most AMF biomarkers were enriched at a soil depth of 0-20 cm in samples collected from the bottom of the slope, which may be a consequence of the fact that plant residues typically accumulate on the soil surface [28,30,31], particularly on relatively at bottom slope. Such residues created high soil, nutrient content, good ventilation and hydrothermal conditions, which is very conducive to the growth of soil microorganisms.…”
Section: Relationships Between Soil Amf Diversity and Soil Propertiessupporting
confidence: 53%
“…Previous studies have investigated AMF communities in the Alps, either based on spore morphology (Read and Haselwandter, ; Oehl et al ., ; Oehl and Körner, ) or on molecular techniques such as DNA fingerprinting and cloning‐sequencing (Sykorová et al ., ; Casazza et al ., ). With the emergence of next‐generation sequencing, and the bypass of cloning steps, it is now possible to study the species diversity and structure of AMF communities in natural populations.…”
Section: Discussionmentioning
confidence: 97%
“…In contrast to the almost absence of a mycorrhizal colonization, we found that all the root samples surveyed in this study were frequently colonized by DSEs, which suggested that these fungi were one of the most common fungal colonizers of the roots of the 'nonmycorrhizal' plant families. Increasing evidence showed that DSEs are ubiquitous, occurring in a variety of habitats ranging from South African coastal plains and lowlands to tropical, temperate, subalpine, alpine, maritime Antarctic and arctic zones (Jumpponen & Trappe 1998;Peterson et al 2004;Vohník et al 2015;Casazza et al 2017;Hewitt et al 2017). In fact, the co-existence between DSE and AMF symbionts occupying terrestrial environments have been extensively documented, but more field surveys also supported that a given plant species in specific microhabitats tends to favor the colonization by DSE over AM fungi (Weishampel & Bedford 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Increasing evidence reveals that a miscellaneous group of ascomycetous anamorphic fungi called dark septate endophytes (DSEs), a term broadly classified as conidial and sterile septate fungal endophytes with diverse morphological features such as dark septate hyphae and microsclerotia, dominantly colonize root tissues intracellularly and intercellularly from the tropics to arctic and alpine habitats (Jumpponen & Trappe 1998;Vohník et al 2015;Casazza et al 2017;Hewitt et al 2017). Even under some extreme environments, for example, old slag heaps resulting from the processing of zinc ores, DSE gradually becomes the most prevailing root colonizers with the decreasing AM colonization at increasing environmental stresses (Deram et al 2008(Deram et al , 2011.…”
Section: Introductionmentioning
confidence: 99%